Fracionamento do manganês em sete solos do estado do Ceará - Araújo, Ivaldo Antonio de (1994)
In seven profiles of soils from Ceará State, Brazil manganese fractioning was carried out, using sequential technique and to determine the available manganese with three extrators. The soils were classified as follows: Areia quartzosa distrófica-AQd, Aluvial Eutrófico-Ae, Bruno Não Cálcico-NC, Cambissolo Eutrófico latossólico-Ce, Latossolo Vermelho Amarelo distrófico-LV, Podzólico Vermelho Amarelo-PV e Podzólico Vermelho Amarelo Eutrófico-PE. The determined fractions were: total manganese, exchangeble manganese, manganese linked to organic complex, manganese oxide, manganese linked to amorphous iron oxide, manganese linked to cristaline iron oxide, residual manganese and available manganese by Mehlich-1, EDTA e DTPA extractors. The total manganese contents varied from 24,9 to 1.041,6 mg/kg, average of 285,7 mg/kg favored by the parental material. A decrease tendency of total manganese content was observed according to the depth, in the Ce, LV, PV and PE profiles, while in the AQd, Ae and NC, a content increase was observed according to the depth. In relation to the total manganese contents, the soils showed a sequence: Ce > NC > Ae > PV > PE > LV > AQd. The lower contents for total manganese in quartz sand sediment origined soils of Barreira group and the higher by the ones originated of calciferoas arenite of Jandaira formation and aluvial sediments of Tertiary. The ones originated of Serra Grande formation arenite, gnaisse saprolitic and silt/clay sediments of Barreira group had intermediary position. The exchangeble manganese and that linked to organic matter were the major ones for available manganese extracted by the Mehlich-1, EDTA and DTPA solutions. The Mehlich-1 and DTPA extractors extracted similar content of available Mn (averages of 24,9 and 24,5 mg/kg, respectively) and higher than EDTA (average 15,2 mg/kg), nevertheless the three results showed a high correlation among each other.